Perfil oxidativo do sangue de cordão umbilical de acordo com a duração do trabalho de parto de gestantes - Vendrame, Silmara Ana (2019)
Oxidative stress is characterized by an imbalance between the production of free radicals and the body's antioxidant capacity. It is known that labor is a process characterized by an increase in oxidative stress, caused by the constant alteration of the oxygen pressure in the placental tissue during the contraction, besides the increase of the oxygen consumption by the skeletal and uterine musculature involved in the contraction. The duration of labor (DOL) is related whit level of oxidative stress, and an already was reported the increase of oxidative parameters during prolonged labor has been reported, which makes it relevant to evaluate the possible oxidative effects in the newborn. Therefore, this study aims to determine markers of oxidative stress in umbilical cord blood of neonates with DOL less than five hours (n = 33) and with DOL greater than five hours (n = 35) and to investigate a possible relation with changes in neonates. The oxidative stress was evaluated by quantification of nitrate / nitrite (NOx), thiobarbituric acid reactive species (TBARS), protein thiol groups (P-SH), vitamin C levels and plasma iron reduction capacity (FRAP) and their correlations besides the determination of the activity of the enzyme δ-ALA-D. By means of the obtained results we can verify that the parameters evaluated both oxidative and antioxidative were significantly higher in umbilical cord blood with DOL> 5h, confirmed by the positive correlation between some parameters, and the activity of the δ-ALA-D enzyme was significantly lower in blood of umbilical cord of newborns of pregnant women with longer duration of labor. There were no significant differences in the physical conditions of the newborns evaluated by Apgar score and birth weight. In conclusion, to our knowledge this is the first paper that describes that the longer labor time, although not considered prolonged, resulted in greater oxidative stress, which may reflect considerably on the health of neonates